The S-Adenosyl-L-Homocysteine Hydrolase Gene ahcY of Agrobacterium radiobacter K84 Is Required for Optimal Growth, Antibiotic Production, and Biocontrol of Crown Gall Disease - Penyalver, Ramón; Oger, Phil M.; Su, Shengchang; Álvarez, Belén; Salcedo, Carmina I.; López, María M.; Farrand, Stephen K. (2017)
Agrobacterium radiobacter K84 is a commercial agent used worldwide to control crown gall disease caused by pathogenic isolates of A. tumefaciens. More than 2,000 transposon insertion derivatives of strain K84 were screened by a standardized greenhouse bioassay to identify mutants defective in biocontrol. Three mutants affected in biocontrol properties were identified. All three mutants displayed normal levels of attachment to tomato seed and root colonization. One of these mutants, M19-164, exhibited partial biocontrol and did not produce detectable levels of agrocin 84. In this mutant, the transposon is located in the agn locus of pAgK84, which codes for agrocin 84 biosynthesis. The second mutant, M19-158, also exhibited partial biocontrol and produced reduced amounts of agrocin 84 as a result of a mutation in a chromosomal gene of unknown function. The third mutant, M9-22, failed to biocontrol, was impaired in both growth in minimal medium and siderophore production, and failed to produce detectable levels of agrocin 84. The chromosomal gene ahcY, which encodes S adenosyl-L-homocysteine hydrolase, was disrupted in this mutant. Expression of a functional copy of ahcY in M9-22 restored all of the altered phenotypes. The fact that all identified biocontrol mutants exhibited a partial or total defect in production of agrocin 84 indicates that this antibiotic is required for optimum biocontrol. This study also identified two chromosomally encoded genes required for agrocin 84 production. That a mutation in ahcY abolishes biocontrol suggests that the intracellular ratio of S-adenosyl-L-methionine to S-adenosyl-L-homocysteine is an important factor for agrocin 84 biosynthesis. Finally, we demonstrate that the ahcY gene in strain K84 is also required for optimal growth as well as for antibiotic production and biocontrol of crown gall disease.